RANCANG BANGUN WEBSITE PENCUCIAN DAN PERAWATAN SEPATU MENGGUNAKAN PHP DAN FRAMEWORK CODEIGNITER - Lailasari, Mita; Widiyaningsih, Wiwied (Jurnal Nasional Teknologi Komputer, 2022)
This research aims to design and build a website which contains information about the business of cleaning and caring shoes. This research is motivated by the function of shoes which are currently a primary human need as a foot protection device and also have become part of a lifestyle. Shoes hygiene is important, and dirty shoes are not only unsightly, but also harmful to health. The condition of clean shoes will certainly make them comfortable to wear at all times. Today, there are many businesses that provide shoe cleaning and care services. Many of these businesses still use manual transactions and customers have to come to the place of business themselves to get their shoes cleaned and cared. With the advancement of internet technology, shoes cleaning and care businesses should created a transactions that can be carried out online and customers doesn’t need to come directly to the place of business because the shoes will be taken by the shoe cleaning and caring business to the customer's home. One of the uses of the internet for this shoe clean and care business is to use a website. This research will discuss the design of a shoe cleaning and care website and the website was created using PHP and the codeigniter framework